AUDITORY VS VISUAL STRATEGIES AMONG KURDISH LEARNERS OF ENGLISH LANGUAGE - Areen Ahmed Muhammed (Universitas Islam Sumatera Utara (UISU), 2020)
When it comes to the case of Kurdish universities regarding teaching styles and methodologies plenty of obstacles and barriers anyone can face not only due to the low level of the majority of the students; but also other factors like religion, interest, grading system, and most importantly low number of references on the subjects area can be the core cause of the issue. One of those points which drove the researcher to write on the common issue was due to the reason that the researcher could not find enough and adequate sources on the subject area; hence, the researcher tried to enrich the referencing system of Kurdish studies of English language in one hand and provide and broaden the horizon of other nationalities regarding Kurdish EFL learners of English and in English taught programs. As a matter of fact, through decades many scholars have been conducting studies on different teaching methodologies and they provided up to four different styles of language teaching. Apart from that, many other linguists enlightened their studies on Far East Asian countries or European. Even if some Middle Eastern studies were taken into consideration; but still, none can be found in the case of Kurdish university students. The current paper was conducted on English department of Charmo University with a total number of 34 participants from three different stages.